The epiphytic Cactaceae Hylocereus setaceus (Salm-Dick ex DC.) ralf bauer seed germination is controlled by light and temperature - Simão, Edson [UNESP]; Socolowski, Fábio [UNESP]; Takaki, Massanori [UNESP] (Brazilian Archives of Biology and Technology, 2007)
O efeito da luz e da temperatura sobre a germinação de sementes de Hylocereus setaceus foi analisado sob condições de incubações isotérmicas. Hylocereus setaceus é uma espécie ameaçada de extinção, que ocorre na Mata Atlântica e florestas estacionais semideciduais. A temperatura mínima para a germinação está entre 5 e 10°C e a máxima entre 45 e 50°C. A temperatura ótima está entre 25ºC e 30°C. A participação do fitocromo, através da resposta de fluência muito baixa, no controle da germinação de sementes foi determinada através de incubações das sementes em um gradiente de fotoequilíbrio do fitocromo. Os resultados apresentados no presente trabalho indicam que sementes de Hylocereus setaceus germinam em uma ampla faixa de temperatura, sob a sombra de vegetação e em áreas abertas, embora não germinem em condições de ausência completa de luz.

The effect of light and temperature on seed germination in Hylocereus setaceus was analyzed by isothermic incubations under continuous white light and darkness. The minimum temperature for germination was between 5 to 10°C and the maximum between 45 to 50°C. The optimum temperaturewais between 25 and 30°C. The involvement of phytochrome, by very low fluence response, in controlled seed germination was attained by incubation in a gradient of photoequilibrium of phytochrome. The results indicated that seeds of H. setaceus germinated in a wide range of temperature, under canopy and in open areas, but in complete darkness they did not germinate.
Keywords: Endangered cactus; phytochrome; seed germination